Analysis of somatic piRNAs in the malaria mosquito Anopheles coluzzii reveals atypical classes of genic small RNAs - Sergei Funikov; Alexander Rezvykh; Natalia Akulenko; Jiangtao Liang; Igor V. Sharakhov; Alla Kalmykova (RNA Biology)
Piwi-interacting small RNAs (piRNA) play a key role in controlling the activity of transposable elements (TEs) in the animal germline. In diverse arthropod species, including the pathogen vectors mosquitoes, the piRNA pathway is also active in nongonadal somatic tissues, where its targets and functions are less clear. Here, we studied the features of small RNA production in head and thorax tissues of an uninfected laboratory strain of Anopheles coluzzii focusing on the 24-32-nt-long RNAs. Small RNAs derived from repetitive elements constitute a minor fraction while most small RNAs process from long noncoding RNAs (lncRNAs) and protein-coding gene mRNAs. The majority of small RNAs derived from repetitive elements and lncRNAs exhibited typical piRNAs features. By contrast, majority of protein-coding gene-derived 24-32 nt small RNAs lack the hallmarks of piRNAs and have signatures of nontemplated 3’ end tailing. Most of the atypical small RNAs exhibit female-biased expression and originate from mitochondrial and nuclear genes involved in energy metabolism. We also identified atypical genic small RNAs in Anopheles gambiae somatic tissues, which further validates the noncanonical mechanism of their production. We discuss a novel mechanism of small RNA production in mosquito somatic tissues and the possible functional significance of genic small RNAs.